Individualized Dosing of Children’s Liquid Medications in the Community Pharmacy Setting: A Survey of Parents and Guardians - Lingxiao Zhai, MS; Stefanie Ferreri, PharmD, BCACP, CDE, FAPhA; Debbie Hiller, PharmD; Jamie Shelly, PharmD; Macary Weck Marciniak, PharmD, BCACP, BCPS, FAPhA (INNOVATIONS in Pharmacy, 2013)
Objectives: 1) To determine parents’ and/or guardians’ interest in having pharmacists provide children’s liquid medications in a pre-measured, individualized dosing device 2) To assess parents’ and/or guardians’ perception of dosing liquid medications for a child. Design: Observational survey Setting: Regional chain pharmacy in North Carolina Participants: > 18 years old, parent/guardian of a child <13 who had prescription filled for liquid medication within the pharmacy chain, responsible for administering child’s liquid medication Intervention: 14 item questionnaire Main Outcome Measure: Interest in pharmacists providing children’s liquid medications in pre-measured, individualized dosing devices Results: 250 questionnaires were mailed; 42 were marked “return to sender” (16.8%), 22 were returned completed (10.6%), and 20 of the 22 met inclusion criteria (9.6%). 95% of study participants reported being interested in having pharmacists provide children’s liquid medications in the proposed dosing device, and 40% were willing to pay for such a service. 90% of respondents reported it is “not at all difficult” to understand the amount of dose a child is to receive, while 55% reported it is “not at all difficult” to measure doses. 25% of respondents reported sometimes using a kitchen spoon to measure a child’s medication. Conclusion: Community pharmacists should explore providing children’s liquid medications in an individualized dosing device, as study results determined parents are interested in and willing to pay for the theoretical device. Further large-scale studies would be beneficial in determining interest in and willingness to pay for the dosing device in various pharmacy settings nationwide.